Asymmetric Information, A Causality Analysis of The Stiglitz - Weiss Model for The Credit Markets, Related to The Textile Sector in Turkey - Tunçay, Cenap Mengü; Gökçe, Atilla (Advances in Social Sciences Research Journal, 2017)
In this study, the problem of asymmetric information and its effects on credit markets have been undertaken within the theoretical framework. It has been tried to test whether the theory of Stiglitz Weiss Model, one of the approaches of theoretical framework of asymmetric information, is convenient for the credit markets, related to textile sector in Turkey due to Granger and Toda Yamamoto Causality Analysis. It has been also determined the direction of causality is convenient with the theory or not. By analyzing Granger and Toda Tamamoto Causality between selected financial ratios, which was chosen from Central Bank of Rebuplic of Turkey, Company Accounts between 1991 – 2014 for the firms, operated in textile sector and credit risk of the sector, it has been tried to determine which financial ratios have causality with the risk of textile sector and the way of causality between these variables. As a result of Granger and Toda Yamamoto Causality Analysis, which have been carried out, it has been found that, for the textile industry in Turkey, the ratio of total credits in short run to total liabilities and the ratio of total credits in long run to total liabilities are affected by the sector’s proportion of liquidated loans to total loans. Due to the mentioned conclusion, some suggestions, belonging to textile sector specifically, have been made by evaluating the strategies, which banks have followed for commercial credit placement, to avoid the default risk of commercial credits.